Challenges in management for sustainability of waqf lands in Malaysia - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah (IIUM Press, 2017)
The word ‘waqf’ is used by many authors to indicate the holding of a certain asset by a person having the trust and preserving it for the benefit of the beneficiary. Being sanctioned by religion as a perpetual charitable donation (sadaqah al-jāriyah), waqf has become an important agenda for the economic empowerment of the Muslims. Emanating from a saying (ḥadīth) of Prophet Muhammad (SAW). narrated by Muslim: “When the son of Adam dies, his deeds are cut off, except in three: perpetual charitable donation and useful knowledge that is made good use of it and the pious son who prays for him”., Muslims believe that waqf is a form of continuous charity where the rewards for this type of charity continue even after the donor’s death, —for as long as people continue to benefit from the waqf. Such is its sustainability.